Recent progresses in porphyrin assisted hydrogen evolution. (17th April 2020) - Joseph, Merin; Haridas, Suja
Abstract: The indiscriminate exploitation of fossil fuels over a period of two centuries has eventually led us to a juncture where search for alternate energy sources and sustainable development has become inevitable. Solar energy remains the most reliable renewable energy source, efficient harnessing of which can serve to meet the future energy demands. Photo-assisted water splitting to generate hydrogen, a potential clean fuel has been the focus of current research in this field. Design and development of suitable materials for efficient solar energy conversion remains the major challenge to be tackled in this aspect. A cost-effective technology for conversion of solar energy is still a distant dream. The present paper attempts a general overview of the basic principles of water splitting with special focus on porphyrin-based systems as promising water splitting systems. Graphical abstract: Image 1 Highlights: A systematic overview of H2 evolution based on porphyrin systems. Unique capability for forming self assembled nanostructures and heterohybrids. Synergetic covalent/noncovalent interactions and efficient electron transfer. High tunability of electronic properties. Compatible for photocatalytic, electrochemical/photoelectrochemical H2 generation.